On the estimation of the volatility-growth link - Klaus Wälde; Andrey Launov; Olaf Posch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
It is common practice to estimate the volatility-growth link by specifying a standard growth equation such that the variance of the error term appears as an explanatory variable in this growth equation. The variance in turn is modelled by a second equation. Hardly any of existing applications of this framework includes exogenous controls in this second variance equation. Our theoretical ndings suggest that the absence of relevant explanatory variables in the variance equation leads to a biased and inconsistent estimate of the volatility-growth link. Our simulations show that this effect is large. Once the appropriate controls are included in the variance equation consistency is re- stored. In short, we suggest that the variance equation must include relevant control variables to estimate the volatility-growth link.
Keywords: E32; O47; O41; 330